Preparation of Nile tilapia skin collagen powder by low-temperature and comprehensive evaluation of hemostasis and wound healing. Issue 2 (February 2023) - Yang, Lintong; Chen, Kaili; Liu, Ping; Kang, Yating; Shen, Shengbiao; Qu, Chenglei; Gong, Shizhou; Liu, Yunguo; Gao, Yonglin
Nile tilapia (hereinafter referred to as tilapia) is a species with high economic value and extensive cultivation. In this study, the low-temperature Nile tilapia skin collagen powder (TSCP) was prepared by liquid nitrogen freeze pulverization. After physical and chemical analysis of its properties, it was found that its characteristics were similar to those of type I collagen. The three-dimensional helix structure of protein peptide is good and non denatured. It shows that cryogenic temperature guarantees the activity of TSCP. In addition, TSCP has good biocompatibility. Specifically, it has good blood compatibility, lacks cytotoxicity, will not cause intradermal stimulation and acute systemic toxicity, and has no obvious rejection after implantation. In the rat liver hemorrhage model and wound repair model, compared with the commercially available bovine collagen powder (BSCP), TSCP has better blood coagulation ability: the shortest hemostatic time (135 s) and wound healing efficiency: the wound healing is obvious on the 14th day. The results of this study indicate that the TSCP is an ideal candidate for hemostatic agents and wound healing dressings.